Możliwości połączenia elementów logorytmiki i metody "Dyna-Lingua M.S." w terapii logopedycznej = Possibilities of combining speech rhythm exercises with the "Dyna-Lingua M.S." method in speech therapy - Mazur, Magdalena (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
Physical activity is natural in children and occurs spontaneously. It promotes children`s growth and development and is as necessary to life as breathing or eating. It is through physical activity that children learn a lot about themselves, determine their place in the space they live in, get to know this space and develop their perception, memory and attention.
Keywords: muzyka; ruch; logopeda; neurologopeda; surdologopeda; logorytmika; mowa; piosenka; metoda psychostymulacyjna; rytmogesty; schematy artykulacyjne; kreacje ruchowe; music; physical activity; speech therapist; neuro speech therapist; speech therapist dealing with deafness and hearing impairment; speech rhythm exercises; speech; song; psychostimulation method; rhythmic gestures; articulation schemes; motor exercises